Kebijakan Deviden Menjadi Moderasi Profitabilitas, Leverage, Free Cash Flow Terhadap Price to Book Value Industri Makanan, Minuman dan Farmasi Tahun 2018 - 2023 - Zaenal Musthofa; Irma Setyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The purpose of this study is to analyze and obtain empirical evidence on the impact of profitability, leverage, and free cash flow on firm value through dividend policy in companies within the Food, Beverage, and Pharmaceutical subsector from 2018 to 2023. The research was conducted on 18 companies using purposive sampling for the period 2018-2023. The data analysis method used was panel data regression, employing Structural Equation Modeling (SEM) with Stata 17 software. The results of the study reveal the following Return on Equity (ROE) has a significant positive effect on Price to Book Value (PBV), Debt-to-Equity Ratio (DER) has a positive but not significant effect on PBV, Free Cash Flow (FCF) has a positive but not significant effect on PBV, Dividend Payout Ratio (DPR) has a significant positive effect on PBV, ROE has a significant positive indirect effect on firm value (PBV) through dividend policy, DER has a negative but not significant indirect effect on PBV through dividend policy, FCF has a positive but not significant indirect effect on PBV through dividend policy. These findings suggest that while profitability, as measured by ROE, directly and indirectly enhances firm value, leverage and free cash flow do not show significant direct or indirect effects on firm value within the observed period and subsector.